The genomic footprint of whaling and isolation in fin whale populations - Sergio F. Nigenda-Morales; Meixi Lin; Paulina G. Nuñez-Valencia; Christopher C. Kyriazis; Annabel C. Beichman; Jacqueline A. Robinson; Aaron P. Ragsdale; Jorge Urbán R.; Frederick I. Archer; Lorena Viloria-Gómora; María José Pérez-Álvarez; Elie Poulin; et al. (Nature Communications, 2023)
Abstract Twentieth century industrial whaling pushed several species to the brink of extinction, with fin whales being the most impacted. However, a small, resident population in the Gulf of California was not targeted by whaling. Here, we analyzed 50 whole-genomes from the Eastern North Pacific (ENP) and Gulf of California (GOC) fin whale populations to investigate their demographic history and the genomic effects of natural and human-induced bottlenecks. We show that the two populations diverged ~16,000 years ago, after which the ENP population expanded and then suffered a 99% reduction in effective size during the whaling period. In contrast, the GOC population remained small and isolated, receiving less than one migrant per generation. However, this low level of migration has been crucial for maintaining its viability. Our study exposes the severity of whaling, emphasizes the importance of migration, and demonstrates the use of genome-based analyses and simulations to inform conservation strategies.